Correction of the specific epithet in Helobdella serendipitous Saglam et al. 2018 (Annelida: Hirudinea) as Helobdella serendipitosa, in accordance with Latin grammar - Saglam, Naim; Shain, Daniel h. (Magnolia Press, 2025)
[Abstract Not Available]